Barriers faced in humanized care in the Intensive Care Units - ICU (Research, Society and Development, 2022)
The advancement of technology has provided better treatment conditions for critically ill patients, but has contributed to the mechanization of care. The objective of this work is to identify the barriers faced by the nursing team for the implementation of humanization in the ICUs. This is a retrospective, descriptive study and a narrative literature review with a search in LILACS, Pubmed and SciELO electronic databases. Scientific articles published in Portuguese and English, from 2015 onwards that contained the described theme were used. It was identified that the dehumanization of care is very present among health professionals because there are several factors that prevent the execution of good care. Mechanization of care, family dissociation, working conditions, implantation of the biomedical model and difficulty in interpersonal relationships were found as main factors. Management and users are also included in the attention of the humanization policy, as their participation in this change is essential. The implementation of the PNH is necessary in order to transform theory into practice.